Comprehensive analysis on design expert modelling for solvent-free coating with halloysite/Malaysian rice/tobacco/linseed oil hybrid system as green inhibitors in maritime applications - Aliyeva, Maryam; Sahin, Fatma Irem; Acarali, Nil (TAYLOR & FRANCIS LTD, 2026)
To ensure environmental sustainability and improve the performance of ship coatings with anti-corrosion and related properties, researchers worldwide focused on developing novel additives and innovative formulations. This issue was critical, as it directly affected ecological balance, economic efficiency, and logistical operations. In the present study, 1% of tobacco, Malaysian rice, halloysite, and linseed oil were incorporated as additives. Their effects on corrosion resistance, adhesion, hydrophobicity, and antifouling performance were evaluated using SEM, TG/DTA, contact angle measurements, and optical microscopy. Coating tests were also carried out to visually examine surface changes. TG/DTA analysis revealed a high decomposition temperature of 403.69 degrees C, even in the presence of tobacco. Contact angle measurements demonstrated hydrophilic behavior with a value of 27 degrees, which was considered advantageous for marine coatings, as hydrophilic surfaces acted as eco-friendly coatings and reduced water resistance, thereby improving ship performance. The Design Expert optimization software was used to generate the necessary statistical tables and graphical responses. The experimental model showed a strong correlation, with an adjusted R-2 value of 0.9693 compared to the predicted R-2 of 0.8325. Furthermore, the Adeq Precision ratio of 17.3215, exceeding the threshold value of 4, confirmed the adequacy of the signal-to-noise ratio in the regression model.
Keywords: Marine coating; Malaysian rice; linseed oil; tobacco; halloysite; ANTIFOULING PROPERTIES; CORROSION-INHIBITOR; PERFORMANCE; EXTRACT; PAINT; CLAY; Engineering; Materials Science; Mechanics